Valorization of Spent Osmotic Solutions by Production of Powders by Spray Drying - Katarzyna Samborska; Alicja Barańska-Dołomisiewicz; Aleksandra Jedlińska; Rui Costa; Konstantinos Klimantakis; Ioannis Mourtzinos; Małgorzata Nowacka (Applied Sciences)
Spent osmotic solutions (sucrose, buckwheat honey, acacia honey, apple juice concentrate, chokeberry juice concentrate, cherry juice concentrate, and mannitol) were tested for their valorization to produce powders by spray drying. Simultaneously, the application of inulin as an alternative carrier was verified. The drying yield varied from 6 to 92%. For acacia honey, apple juice concentrate, chokeberry juice concentrate, and cherry juice concentrate, high stickiness was observed, which resulted in low yield and the production of significantly bigger particles of regular size distribution, higher hygroscopicity and bulk density, and better flowability. Sucrose, acacia honey, and mannitol were dried with lower stickiness, and the physical properties of the powders were acceptable. However, the yield of mannitol drying was low due to very small particles, low bulk density, and low cyclone efficiency. Therefore, sucrose and buckwheat honey solutions can be successfully spray dried using inulin as a carrier to produce powders suitable for further food applications. However, for the other tested materials, alternative carriers should be considered to reduce stickiness during drying.